Training needs of teachers of the first cycle of basic education for digital skills in the field of distance education - موسى غنى محمد جهاد (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The aim of the research is to identify the degree of training needs of teachers of the first cycle of basic education, for digital skills in the field of distance education. To achieve this goal, the descriptive approach was used, and a questionnaire consisting of (43) items was prepared under three axes. After verifying the validity and reliability of the questionnaire, it was applied to a random sample, which consisted of (255) male and female teachers of the first cycle of basic education in the schools of Damascus Governorate for the academic year 2022-2023. The search concluded with the following results: The most in need of digital skills among teachers of the first cycle (the research sample) is related to the axis (electronic content design), as its arithmetic average reached (2.50), and with a relative weight of (83.33%), and with a high degree of need, then the axis (basic computer skills), Its arithmetic average reached (2.41), with a relative weight (80.33%), and a high degree of need, then the axis (management of virtual classrooms in distance education), which came with an arithmetic average of (2.37), and with a relative weight of (79%), and a high degree of need also. The overall result of the training needs related to the three axes also came with a high degree of need, as the arithmetic mean was (2.42), with a relative weight of (80.66%). There are statistically significant differences between the average scores of the answers of teachers of the first cycle of basic education on the items of the questionnaire for training needs for digital skills in the field of distance education, due to the educational qualification variable in favor of teachers holding a university degree. There are statistically significant differences between the average degrees of the answers of teachers of the first cycle of basic education on the items of the questionnaire of training needs for digital skills in the field of distance education due to the variable of training courses, in favor of teachers who followed training courses. Based on the results of the research, a set of proposals were presented regarding the need to hold training courses for teachers of the first cycle of basic education, with the aim of training teachers to employ digital skills in the field of distance education, which can be an alternative to direct education face to face in light of crises, especially the Corona crisis and the closure of Universities and schools, and the need to conduct more studies in this field.